Challenges and opportunities : the Wal-Mart effect in South Africa. - Alexander, Kelly (My University, 2012)
This research aims to interrogate the question of “Challenges and Opportunities: The Wal-Mart Effect In South Africa”. The research aims to investigate the potential effect that Wal-Mart will have on labour, the local economy and consumers in South Africa. This is in the broader context of neo-liberal globalisation. The key findings regarding stakeholders’ engagement around the issues of Wal-Mart’s arrival and the role of the state, the resistance by local and international trade unions, the detrimental effects on the local and informal economies, the failure of the South African macro-economic policy environment and the positive effect that Wal-Mart will have on consumers are all presented and analysed. The key message that emerges is that neo-liberal policies in South Africa have eroded labour rights, and hampered the development of the local economy. Although Wal-Mart’s arrival could exacerbate this, it simultaneously provides a springboard for resistance and a unique opportunity to rethink the policy framework of the country. In a country with high levels of poverty, Wal-Mart may force local retailers to become increasingly competitive and to provide goods to consumers at a lower cost – which is obviously something that will benefit local consumers. Furthermore Wal-Mart’s strength is in its systems and processes which is something that could benefit South African companies as they learn from the giant retailer. Wal-Mart’s entry into South Africa will have to be carefully managed and monitored to ensure the maximum benefit for all stakeholders, and to limit the adverse effects of the retail giant.
Keywords: Wal-Mart; South Africa